ACCESSIBILITY ISSUES RELATING TO ELDERLY IN INDIA- A STUDY - Uma, V.R. (International Journal of Research -GRANTHAALAYAH, 2018)
Older people are the only growing segment of world’s population. They are one of the important consumers and contributors to the economic and social lives of the member states of this world. As citizens, they should share the same rights as people of other ages to access to every part of our society. Yet, the reality of life is that older people face barriers in some of the most basic areas of life –areas which other members of our community can access at will – just because of their age. older people and indeed people from other age groups, face unnecessary discrimination in other parts of their lives and this is neither in the interests of individuals or in the interest of our economy and society. In an ageing society we need a cultural and policy framework which breaks down barriers to participation rather than erecting and permitting them, and maximises the ability of individuals to participate in economic and social activity, whatever their personal characteristics.